Achievement Motivation Training in a Community College Setting. Effects on Personality and Educational Variables - Reimanis, Gunars ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
The Corning Community College, having an open-door admissions policy, has been offering a course in achievement motivation for the past two years. The course, requiring about forty-five hours of participation, was started on an experimental basis with specially selected high-risk entering students during the summer of 1969. The main purposes of the course have been: (1) to help students adjust to college life, (2) to provide them with skills in self-exploration that facilitate their career planning, and (3) to increase their motivation in pursuit of their goals. This paper presents research data that were collected over a two year period to assess the effects of the achievement motivation course on several educationally relevant variables. It was hypothesized that achievement motivation training would give rise to increased achievement motivation. The results generally supported the hypothesis, but it was strongly suggested that trainer and trainee personalities have to be considered to gain a more complete understanding of the effects of achievement motivation training. (Author/BW)
ERIC Note: Paper presented at the Interamerican Congress of Psychology, Panama City, December 15, 1971.
Microfiche.
Keywords: Academic Achievement; Achievement Gains; Achievement Rating; Achievement Tests; Behavior Change; Goal Orientation; Learning Motivation; Low Achievement; Motivation; Personality; Student Improvement; Teacher Influence; Underachievement